Phase evolution and electrical properties of lead zirconate titanate thin films grown by using a triol sol-gel route - Thountom S. (2014)
Lead zirconate titanate (PZT) precursor sols were prepared using a triol based sol-gel route. Inorganics salts metal alkoxides lead acetate trihydrate [Pb(OOCCH3)2·3H2O], titanium (IV) isopropoxide [Ti(OCH(CH3)2)4], and zirconium n-propoxide [ZrOC3H7)4] were used as starting materials. Thin films were deposited by spin coating onto Pt/Ti/SiO2/Si substrates. The samples were pre-heated (pyrolysis) on a calibrated hotplate over the temperature range of 200-400 °C for 10 min then firing at a temperature of 600 °C for 30 min. Randomly-oriented PZT thin films pre-heated at 400 °C for 10 min and annealed at 600 °C for 30 min showed well-defined ferroelectric hysteresis loops with a remanent polarization of 27 μC/cm2 and a coercive field of 115 kV/cm. The dielectric constant and dielectric loss of the PZT films were 621 and 0.040, respectively. The microstructures of the thin films are dense, crack-free and homogeneous with fine grains about 15-20 nm in size. © 2008 Elsevier Ltd and Techna Group S.r.l.